The Legal Protection for Whistleblowers on Corruption Crimes in Indonesia - Sulastri, Lusia (Jurnal Daulat Hukum, 2023)
The crime of corruption, which is also classified as an extraordinary crime or referred to as an extraordinary crime, has characteristics and characteristics related to the power of a person holding a position in a government system, from the village government system to the central government system. Efforts to reveal criminal acts of corruption require the role of witnesses regarding these crimes who can be reported by the reporter. This research used literature study with the doctrinal approach. In addition, this study also examines the ideal legal protection for whistleblowers for corruption. The results of the study show that legal protection for whistleblowers for criminal acts of corruption is not running well, as evidenced by the determination of the status of the suspect Nurhayati for Corruption Crimes in Cirebon Regency. This happens because there is no common perception of the position of the Whistleblower on Corruption Crimes as a subject protected by law between the police and the Prosecutor's Office. The ideal legal protection for whistleblowers for criminal acts of corruption is to build legal protection for whistleblowers that is integrated and obeyed by law enforcement officers. The provision of witness protection must of course start from law enforcement who is the spearhead of law enforcement, namely the police.